(untitled) - Vo Chau Ngan Nguyen (Cần Thơ, 2012)
The study focuses on waste management in the Mekong Delta of Vietnam through the application of biogas plants to livestock and agricultural waste treatment.
Keywords: Wastewater,Environmental protection,Xử lý nước thải